Amino functionalized magnetic covalent organic framework for magnetic solid‐phase extraction of sulfonylurea herbicides in environmental samples from tobacco land. Issue 10 (8th March 2022) - Tian, Cong; Wu, Zhekuan; He, Man; Chen, Beibei; Hu, Bin
Abstract : An amino‐functionalized magnetic covalent organic framework composite TpBD‐(NH2 )2 @Fe3 O4 (Tp=Tp1, 3, 5‐triformylphloroglucinol, BD‐(NH2 )2 is 3, 3', 4, 4'‐biphenyltetramine) was prepared by post‐synthesis modification. Due to its abundant benzene rings and amino groups, large specific surface area and porous structure, the prepared TpBD‐(NH2 )2 @Fe3 O4 exhibits high extraction efficiency toward sulfonylurea herbicides. Based on this, a new method of magnetic solid‐phase extraction with TpBD‐(NH2 )2 @Fe3 O4 as the sorbent combined with high‐performance liquid chromatography and ultraviolet detection was developed for trace analysis of sulfonylurea herbicides in environmental water, soil and tobacco leaves samples from tobacco land. Under the optimized conditions, the limits of detection within 0.05–0.14 μg/L were achieved with a high enrichment factor of 217‐260‐fold, and the relative standard deviations were 4.9–7.5% ( n  = 7, c = 0.5 μg/L). The linear range was around three orders of magnitude with the square of correlation coefficient higher than 0.9936. The method was applied to analyze five sulfonylurea herbicides in the environmental water, soil, and tobacco leave samples collected from tobacco land. No sulfonylurea herbicides were detected in these samples. The recoveries of target sulfonylurea herbicides in spiked environmental water, soil, and tobacco leaf samples were found in the range of 90.7–104, 70.7–99.0, and 59.3–97.8%, respectively. The results illustrate that the established TpBD‐(NH2 )2 @Fe3 O4 ‐magnetic solid‐phase extraction‐ high‐performance liquid chromatography–ultraviolet detection method is efficient for the analysis of trace sulfonylurea herbicides in environmental samples.